1996
DOI: 10.1111/j.1365-2044.1996.tb15005.x
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anaesthesia with propofol or inhalational anaesthesia with isoflurane for major abdominal surgery: Recovery characteristics and postoperative oxygenation—an international multicentre study

Abstract: SummaryTwo hundred und teri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Previous studies have demonstrated significant changes in systemic hemodynamics [32] and systemic oxygenation [33] during and immediately following major surgery, which may potentially alter ocular oxygenation. Since blood is drawn from the femoral artery to monitor systemic arterial PO 2 and establish the physiologic condition of animals during experiments, it is beneficial to determine the effect of this surgical procedure on retinal oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated significant changes in systemic hemodynamics [32] and systemic oxygenation [33] during and immediately following major surgery, which may potentially alter ocular oxygenation. Since blood is drawn from the femoral artery to monitor systemic arterial PO 2 and establish the physiologic condition of animals during experiments, it is beneficial to determine the effect of this surgical procedure on retinal oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoxia, defined as an S p O 2 of less than 94%, was observed for 1–1.5% of the duration of measurement in this study in both groups. Low oxygen saturations are a common occurrence in the postoperative period after major surgery even in the absence of intrathecal or extradural opioids [22, 23]. The low incidence and the lesser degree of postoperative desaturation in our and other obstetric studies is probably due to the lower abdominal nature of the surgery and lower intra‐abdominal pressure after delivery of the baby.…”
Section: Discussionmentioning
confidence: 76%
“…Transition from sedation to anaesthesia by TCI is smooth and simple, and permits improved haemodynamic stability compared with other methods [23]. Total intravenous anaesthesia, with a propofol/opioid‐based technique allows faster emergence with superior recovery [24] compared with volatile‐based anaesthesia [25]. This is especially important in the immediate postoperative management of a patient with a difficult airway.…”
Section: Discussionmentioning
confidence: 99%